STRATEGI PENGEMBANGAN PERIKANAN TANGKAP DI KABUPATEN KEPULAUAN TALAUD - Jeti Pulu; M. S. Baskoro; D. R. Monintja; B. H. Iskandar; A. Fauzi (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2011)
This paper is discussing the continuation of previous research result in Talaud Island Regency that analyzed the loss due to illegal fishing activities in the area. Simulation result shows that if there is no illegal fishing, fisheries economic potential in Talaud is estimated to be in about IDR 7 billion or even might reach IDR 10 billion, but if this illegal fishing activities increased with acceleration, then in in the coming year-20th that potential will be negative. This means an economic loss of Talaud Regency. By means of a SWOT analysis, at least three main strategies are obtained those are as follows: increasing local budget alocation for marine and fisheries sectors, fisheries bussiness cooperation between Indonesia and Filiphina to eliminate illegal fishing practices and empowerment of the local community.